Empowering The Head of Poor Women's Family in Efforts to Improve Welfare ( Case Study for Empowering The Head of Poor Women's Family in Sidoarjo District ) - Heri Sudarsono (Enrichment : Journal of Management, 2021)
Poverty is a complex problem, which is interrelated with one another, including: low skill levels, low capital ownership, low employment opportunities, low income levels, low education levels, low health levels, low productivity . One approach to solving the problem of poverty is through a community empowerment approach ( community empowerment ). Through this empowerment approach, it provides opportunities for the community to play an active role in development by developing their potential as the basic capital of development, and giving full authority to the community in making decisions according to their wants and needs. Penanggu circles in poverty for Sidoarjo regency , one of them reached by way of women's empowerment, by providing training for Poor Women Headed Households that a partnership with several employers. What is interesting about the empowerment program in Sidoarjo is that the target is aimed at women as the head of poor families, on the grounds that the basis for selecting the program is that women have a position in a country, society and even in the household. Based on the findings from the results of data processing on the variables studied, it can be concluded that the implementation of poverty alleviation with an empowerment approach to the Head of Poor Women's Family in Sidoarjo is still not optimal in reducing the number of poor people, therefore there needs to be an increase, especially in the entrepreneurial aspect of women